2021
DOI: 10.7202/1080809ar
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Cycle of Trauma – Koori Parenting, What Works for Us

Abstract: Objective: To develop an understanding of parenting strategies used by Aboriginal Australian parents impacted by colonisation and other forms of adversity to break cycles of trauma within families. Design: “Yarning circles” involving qualitative interviews with six Aboriginal parents were conducted. Parents who identified as having experienced childhood histories of trauma and historical loss were asked about parenting strategies that helped them to break cycles of intergenerational trauma. Interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…There were 29 studies that reported on the wellbeing of Indigenous youth in Australia [ 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 ]. Our thematic analysis identified seven overarching components of wellbeing for this population: basic needs; relationships; culture; aspirations for the future; identity; recreational activities and interests; and physical and mental health.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There were 29 studies that reported on the wellbeing of Indigenous youth in Australia [ 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 ]. Our thematic analysis identified seven overarching components of wellbeing for this population: basic needs; relationships; culture; aspirations for the future; identity; recreational activities and interests; and physical and mental health.…”
Section: Resultsmentioning
confidence: 99%
“…The provision of basic material needs and services is seen as an essential foundation upon which positive wellbeing can be realised for Indigenous youth in Australia [ 96 , 98 ]. Safe and stable housing is viewed as a key protective element against potential negative influences such as food insecurity, unsafe environments, transience, and exposure to communicable disease and the child welfare system [ 82 , 83 , 89 , 98 , 103 , 106 , 108 ]. Accommodation security can be undermined by unaffordable housing, discrimination when entering the rental market, and overcrowding, affecting Indigenous youths’ experience of safe housing [ 83 , 96 , 101 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations